Therapist or mental skills coach? How to decide - Herzog, T.; Hays, K. F. (The Sport Psychologist, 2012)
This article addresses the challenging conundrum of when to offer psychotherapy versus mental skills training. To highlight aspects of this dilemma, we describe actual cases that illustrate different ways in which clients present and practitioners may respond: (1) mental skills training shifting to therapy; (2) therapeutic work shifting to mental skills training; (3) simultaneous work between two practitioners; or (4) alternating services from the same practitioner. A variety of intervention methods are used based on a number of theoretical orientations and perspectives. The article concludes with some recommendations that may assist the performance oriented practitioner in decision-making regarding the delicate balance between therapy and mental skills training. Suggestions relate specifically to the nature of the referral, the client`s preferences, the practitioner`s perspective and skill sets, a continuous process of appraisal and adaptation, and the central importance of the athlete-practitioner relationship.